Digital Critique Terminology and Mechanisms - Saiah, Nadia Lekdjaa Djelloul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Technology has evolved and Arabic language sciences have evolved; So that the new mediator influenced them and contributed to changing their patterns, multiple forms and diversity of contents, and the interconnected text or interactive, bifurcated text through which all senses correspond and time relates to the place in a very different format than usual, sometimes making the reader a de facto partner in the creative process. The value and importance of research: the emergence of new patterns such as interactive story, or digital narrative, has made it urgent to build a new approach to reading and analysing these new creative patterns according to a new approach Research objectives: This research seeks to provide a practical vision and propose procedural mechanisms for the study and analysis of texts The problem of research: What are the tools of blue text and what are its procedural mechanisms? How can readers of digital text read an objective suitable for it? Research results: an objective study of the interactive text cannot be reached by analysing it with the same approach adopted in reading the paper text; This is because they are different